1992
DOI: 10.1007/bf01542997
|View full text |Cite
|
Sign up to set email alerts
|

Sexual activities and preferences in a United Kingdom sample of 16 to 20-year-olds

Abstract: Data are reported on the sexual behavior of a random sample of 2171 youth, 16-20 years old, in two locations in the U.K. Lower bound prevalence estimates for a range of specific sex acts are presented with discussion of the likely biases in the data. Given concerns about the spread of HIV through the heterosexual population, emphasis is given to the nontrivial estimates of a number of potential transmission risk behaviors, in particular, heterosexual anal penetration. Data are also presented suggesting that ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 25 publications
1
15
1
Order By: Relevance
“…A representative sample of one gender in a population is expected to differ from a representative sample of the opposite gender's partners, at least in relation to age and number of partners . In studies where representativeness of couples could be obtained, similar reporting for both genders has been found (Breakwell and Fife-Schaw, 1992). Such a situation is very improbable in our case, since the multiple partners of the women studied here are not necessarily men with multiple partners, and vice versa.…”
Section: Gender Reporting Differencessupporting
confidence: 65%
See 3 more Smart Citations
“…A representative sample of one gender in a population is expected to differ from a representative sample of the opposite gender's partners, at least in relation to age and number of partners . In studies where representativeness of couples could be obtained, similar reporting for both genders has been found (Breakwell and Fife-Schaw, 1992). Such a situation is very improbable in our case, since the multiple partners of the women studied here are not necessarily men with multiple partners, and vice versa.…”
Section: Gender Reporting Differencessupporting
confidence: 65%
“…These figures are rather low compared to other surveys (Breakwell and Fife-Schaw, 1992;Catania et al, 1990). The highest rates were from women, for questions on practice-by-practice condom use.…”
Section: Limitationscontrasting
confidence: 55%
See 2 more Smart Citations
“…The small number of studies with nonhomeless youth that have included a measure of anal sex have revealed lower levels of anal sex (and unprotected anal sex) than were found in this group (e.g. Rosenthal et al 1990, Breakwell andFife-Shaw 1992).…”
Section: Survey Resultsmentioning
confidence: 94%